"Antifeminist 'feminism'": the case of French "decolonial intersectional feminism". (4th May 2022) - Binard, Florence
ABSTRACT: The object of this article is to show that in recent times of crisis – notably in view of the repeated terrorist attacks that have taken place in France – a form of insidious backlash on feminism has operated through antifeminist appropriations of feminism by self-named French "decolonial intersectional feminists" whose antiracist stance and praxis leads them to sometimes distort and even betray the goals of feminism. Contrary to their purported use of intersectionality as a pluri-identity analytical tool, these "feminists" assign people to a single dominant primary identity, based either on their religion or the colour of their skin, which leads them to defend antifeminist views. 1